CYTOLOGICAL VARIATION OF (AAG)7 REPEAT ON LETTUCE CHROMOSOMES BY FLUORESCENCE IN SITU HYBRIDIZATION (FISH) - Widarmi, Winny Dewi; Kikuchi, Shinji; Sassa, Hidenori; Koba, Takato (International Journal of Biosciences and Biotechnology; Vol 8 No 2 (2021): International Journal of Bioscience and BiotechnologyDO - 10.24843/IJBB.2021.v08.i02.p06, 2021)
Cytological studies using fluorescence in situ hybridization (FISH) technique provides phylogenetical information in closely related taxa and have been widely applied for karyotyping and studying chromosomal organization and evolution in plant species. In the present study, FISH using a microsatellite sequence of (AAG) 7 as the probe was performed in order to discriminate the chromosomes in four Lactuca species, i.e. , L. sativa, L. serriola , L. salign a, and L. virosa . The experiment was carried out in April to September 2018 at Laboratory of Genetic and Plant Breeding of Breeding of Graduate School of Horticulture, Chiba University, Japan. Different distribution patterns of (AAG) n signals were shown on the chromosomes in the four Lactuca species studied, In L. sativa and L. serriola , FISH with (AAG) 7 sequences revealed dispersed distribution patterns with one pair of bright signals, respectively. While in L. saligna and L. virosa, distinct signals with different intensities were observed in two pairs of chromosomes of L. saligna and five pairs of chromosomes of L. virosa . In conclusion, the AAG repeat signals could be used as cytogenetic landmarks for chromosome identification in Lactuca species.